Efektivitas Penggunaan Aplikasi Zoom dalam Pembelajaran Mata Kuliah Hiwar di STAI Ali Bin Abi Thalib Surabaya - Moch. Danu Kurniadi (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2021)
Since the COVID-19 pandemic has spread widely, universities must adjust their curriculum programs to an online system that is supported by various existing media. One of the media that is often used is the Zoom Meeting application. STAI Ali Bin Abi Talib as one of the universities in the field of education that implements an online system in its program during this pandemic has also used the Zoom Meeting application in its learning activities. However, so far the implementation of the Zoom meeting application as an official medium on campus that is used many times for teaching and learning, there has been no evaluation, especially regarding Hiwar's courses. This evaluation is a study that aims to determine the effectiveness of using the Zoom application program in the Hiwar course. This evaluation is also to find out what problems can be revealed while using this application program. This research is a descriptive field research through a qualitative approach with interviews, observations, and questionnaires. The research results obtained are, (1) The online learning system using the Zoom Meeting Application, especially the Hiwar subject, is literally effective, judging from the percentage of correspondence, the learning program is very well implemented, the level of activeness and understanding of students in the subject matter gets an assessment of around 91.7%. The learning evaluation was carried out well by Zoom Meeting and achieved a rsting around 86.1% (2) there are still many other obstacles in using this program, especially regarding the limited internet quota, signals, gadgets, and an unsupported environmental system.